2013
DOI: 10.11594/jtls.03.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fertility effect of various plants at Dayak Tribe to Swiss Webster Mice

Abstract: Blumea balsamifera, Croton tiglium, Metroxylon sagu, and Fagraea racemosa are used as traditional antifertility of Dayak people in Central Kalimantan. These study aims at finding out the potential plants as antifertility with the use on Swiss Webster (SW) mice. Extracts of B. balsamifera, C. tiglium, M. sagu, and F. racemosa were administered by gavage at the dose level of 0.26 mg/kg body weight (b.w) to female of SW mice for 8 days to examine their estrous cycle. To determine the anti-fertility, the procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…A decrease in the corpus luteum and fetus was attributed to the anti-infertility effect of the extract against the inhibition of folliculogenesis. Researchers also reported that B. balsamifera extract had promising anti-infertility activity compared to other plant extracts used in this study [66].…”
Section: Anti-infertility Activitysupporting
confidence: 53%
See 1 more Smart Citation
“…A decrease in the corpus luteum and fetus was attributed to the anti-infertility effect of the extract against the inhibition of folliculogenesis. Researchers also reported that B. balsamifera extract had promising anti-infertility activity compared to other plant extracts used in this study [66].…”
Section: Anti-infertility Activitysupporting
confidence: 53%
“…Various experimental studies both in vitro and in vivo have reported the pharmacological activities of B. balsamifera, such as antioxidant, cytotoxic, antimicrobial, antifungal, anti-inflammatory, and hypolipidemic. Table-2 [13,22,56,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] summarizes some studies on the pharmacological activity of B. balsamifera.…”
Section: Progress On Pharmacological Studies Of B Balsamiferamentioning
confidence: 99%
“…Some of the compounds found in plants are useful as anti-fertility include steroids, flavonoids and alkaloids. 17 There are no reports that the Langsat's bark containing these components, so use as a drug anti-fertility not appropriate.…”
Section: Discussionmentioning
confidence: 99%